The impact of supervisor’s roles in the training program on the transfer of training / Sufi Farhana Mohd Kamari - Mohd Kamari, Sufi Farhana (Faculty of Business and Management, 2018)
Supervisors as a person who are responsible to monitor and supervise their subordinates in the organization. They need to make sure every newly learning from the training programs must be transferred into the job effectively. So that, the supervisors need to pay more attention towards how the knowledge, skills and abilities can be transfer to the workplace. In this research, the researcher conducted to examine the relationship between supervisor’s roles in the training programs on the transfer of training.